Pengaruh Struktur Kewenangan, Karakteristik Sistem Informasi Keuangan Daerah dan Perilaku Manajer Terhadap Kesadaran Akan Biaya (Studi Empiris Pada Pemerintah Kota Solok) - Mutiara Candra (Ekonomis: Journal of Economics and Business, 2020)
This research aimed to identify and to get empirical evidence of the effect of the structure of authority that is broken down into formal and informal authority structures, the characteristics of regional financial information systems and managers' behavior on cost consciousness. This study was 37 SKPD registered in Solok city with a total sample of 74 people consisting of leaders and treasurer office / agency / office at SKPD in Solok city. Dependent variable in this research is the cost consciousness and independent variable that is authority structure (structure of formal authority and structure of informal authority), Characteristics of regional financial information systems and manager behavior. The hypothesis is tested by using multiple regression analysis using SPSS version 14. This study shows the test results that manager behavior does not affect the cost consciousness, while formal, informal authority structures and Regional financial information systems have a significant effect on the cost consciousness.